Kingdom(s) Come: Character Remediations and Polyperspectivity of the Final Fantasy franchise in Kingdom Hearts and Kingdom Hearts II - McLean, James (Loading, 2022)
Over twenty years since its original release, Final Fantasy VII (Square 1987) fans continue to debate the video game’s world and characters as they are mixed and remixed into new licensed products. This article explores the fan metanarrative that circulates the story, ludology, and industry discourses that bind Final Fantasy VII. It will demonstrate how fan practices operate within community spaces to locate, present, and police both knowledge and meanings about a fictional world that itself is continually being reshaped by the transmedia production milieu. This article explores the ongoing fan debates circulating characters Cloud, Tifa, and Aerith from Final Fantasy VII, and their respective remixing into the Kingdom Hearts franchise. Through a discourse analysis (Gee, 2007) of online Western fan bases, published above-the-line production interviews (Mayer et al. 2009), and self-reflexive experiences (Hills 2002), I seek to demonstrate the complexity of fan practices and how they attempt to locate (and generate) narrative coherency. I will argue that fans do not simply enjoy games for their variance in gameplay and story but seek a better understanding of a growing fictional world that is complex and is subject to sanctioned rewrites. Drawing on Eiji Ōtsuka’s theories on world and variation (2010), this article will demonstrate how fans can function as textual barristers in their attempts to untangle the media mix (Steinberg, 2012) of Final Fantasy VII through its ongoing reiterations, adaptations, and world-sharing with Kingdom Hearts series.